Step
*
1
2
of Lemma
near-inverse-of-increasing-function
1. f : ℝ ⟶ ℝ
2. n : ℕ+
3. M : ℕ+
4. z : ℝ
5. [n@0] : ℕ
6. ∀[m:ℕn@0]
     ∀a,b:ℤ.
       ∀k:ℕ+
         (∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])) supposing 
            ((z ≤ f[(r(b))/k]) and 
            (f[(r(a))/k] ≤ z) and 
            (∀x,y:ℝ.
               (((r(a))/k ≤ x)
               
⇒ (x < y)
               
⇒ (y ≤ (r(b))/k)
               
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))) and 
            (((M * (b - a)) - k) ≤ m)) 
       supposing a < b
7. a : ℤ
8. b : ℤ
9. a < b
10. k : ℕ+
11. ((M * (b - a)) - k) ≤ n@0
12. ∀x,y:ℝ.
      (((r(a))/k ≤ x)
      
⇒ (x < y)
      
⇒ (y ≤ (r(b))/k)
      
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))
13. f[(r(a))/k] ≤ z
14. z ≤ f[(r(b))/k]
15. ¬((M * (b - a)) ≤ k)
⊢ ∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])
BY
{ ((Evaluate ⌜m = (a + b) ∈ ℤ⌝⋅ THENA Auto)
   THEN (Evaluate ⌜j = (2 * k) ∈ ℤ⌝⋅ THENA Auto)
   THEN (InstLemma `nearby-cases` [⌜n⌝;⌜f[(r(m))/j]⌝;⌜z⌝]⋅ THENA Auto)
   THEN SplitOrHyps) }
1
1. f : ℝ ⟶ ℝ
2. n : ℕ+
3. M : ℕ+
4. z : ℝ
5. [n@0] : ℕ
6. ∀[m:ℕn@0]
     ∀a,b:ℤ.
       ∀k:ℕ+
         (∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])) supposing 
            ((z ≤ f[(r(b))/k]) and 
            (f[(r(a))/k] ≤ z) and 
            (∀x,y:ℝ.
               (((r(a))/k ≤ x)
               
⇒ (x < y)
               
⇒ (y ≤ (r(b))/k)
               
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))) and 
            (((M * (b - a)) - k) ≤ m)) 
       supposing a < b
7. a : ℤ
8. b : ℤ
9. a < b
10. k : ℕ+
11. ((M * (b - a)) - k) ≤ n@0
12. ∀x,y:ℝ.
      (((r(a))/k ≤ x)
      
⇒ (x < y)
      
⇒ (y ≤ (r(b))/k)
      
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))
13. f[(r(a))/k] ≤ z
14. z ≤ f[(r(b))/k]
15. ¬((M * (b - a)) ≤ k)
16. m : ℤ
17. m = (a + b) ∈ ℤ
18. j : ℤ
19. j = (2 * k) ∈ ℤ
20. f[(r(m))/j] < z
⊢ ∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])
2
1. f : ℝ ⟶ ℝ
2. n : ℕ+
3. M : ℕ+
4. z : ℝ
5. [n@0] : ℕ
6. ∀[m:ℕn@0]
     ∀a,b:ℤ.
       ∀k:ℕ+
         (∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])) supposing 
            ((z ≤ f[(r(b))/k]) and 
            (f[(r(a))/k] ≤ z) and 
            (∀x,y:ℝ.
               (((r(a))/k ≤ x)
               
⇒ (x < y)
               
⇒ (y ≤ (r(b))/k)
               
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))) and 
            (((M * (b - a)) - k) ≤ m)) 
       supposing a < b
7. a : ℤ
8. b : ℤ
9. a < b
10. k : ℕ+
11. ((M * (b - a)) - k) ≤ n@0
12. ∀x,y:ℝ.
      (((r(a))/k ≤ x)
      
⇒ (x < y)
      
⇒ (y ≤ (r(b))/k)
      
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))
13. f[(r(a))/k] ≤ z
14. z ≤ f[(r(b))/k]
15. ¬((M * (b - a)) ≤ k)
16. m : ℤ
17. m = (a + b) ∈ ℤ
18. j : ℤ
19. j = (2 * k) ∈ ℤ
20. z < f[(r(m))/j]
⊢ ∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])
3
1. f : ℝ ⟶ ℝ
2. n : ℕ+
3. M : ℕ+
4. z : ℝ
5. [n@0] : ℕ
6. ∀[m:ℕn@0]
     ∀a,b:ℤ.
       ∀k:ℕ+
         (∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])) supposing 
            ((z ≤ f[(r(b))/k]) and 
            (f[(r(a))/k] ≤ z) and 
            (∀x,y:ℝ.
               (((r(a))/k ≤ x)
               
⇒ (x < y)
               
⇒ (y ≤ (r(b))/k)
               
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))) and 
            (((M * (b - a)) - k) ≤ m)) 
       supposing a < b
7. a : ℤ
8. b : ℤ
9. a < b
10. k : ℕ+
11. ((M * (b - a)) - k) ≤ n@0
12. ∀x,y:ℝ.
      (((r(a))/k ≤ x)
      
⇒ (x < y)
      
⇒ (y ≤ (r(b))/k)
      
⇒ ((f[x] ≤ f[y]) ∧ (((y - x) ≤ (r1/r(M))) 
⇒ ((f[y] - f[x]) ≤ (r1/r(n))))))
13. f[(r(a))/k] ≤ z
14. z ≤ f[(r(b))/k]
15. ¬((M * (b - a)) ≤ k)
16. m : ℤ
17. m = (a + b) ∈ ℤ
18. j : ℤ
19. j = (2 * k) ∈ ℤ
20. |f[(r(m))/j] - z| ≤ (r1/r(n))
⊢ ∃c:ℤ. (∃j:ℕ+ [((|f[(r(c))/j] - z| ≤ (r1/r(n))) ∧ ((r(a))/k ≤ (r(c))/j) ∧ ((r(c))/j ≤ (r(b))/k))])
Latex:
Latex:
1.  f  :  \mBbbR{}  {}\mrightarrow{}  \mBbbR{}
2.  n  :  \mBbbN{}\msupplus{}
3.  M  :  \mBbbN{}\msupplus{}
4.  z  :  \mBbbR{}
5.  [n@0]  :  \mBbbN{}
6.  \mforall{}[m:\mBbbN{}n@0]
          \mforall{}a,b:\mBbbZ{}.
              \mforall{}k:\mBbbN{}\msupplus{}
                  (\mexists{}c:\mBbbZ{}
                      (\mexists{}j:\mBbbN{}\msupplus{}  [((|f[(r(c))/j]  -  z|  \mleq{}  (r1/r(n)))
                                    \mwedge{}  ((r(a))/k  \mleq{}  (r(c))/j)
                                    \mwedge{}  ((r(c))/j  \mleq{}  (r(b))/k))]))  supposing 
                        ((z  \mleq{}  f[(r(b))/k])  and 
                        (f[(r(a))/k]  \mleq{}  z)  and 
                        (\mforall{}x,y:\mBbbR{}.
                              (((r(a))/k  \mleq{}  x)
                              {}\mRightarrow{}  (x  <  y)
                              {}\mRightarrow{}  (y  \mleq{}  (r(b))/k)
                              {}\mRightarrow{}  ((f[x]  \mleq{}  f[y])  \mwedge{}  (((y  -  x)  \mleq{}  (r1/r(M)))  {}\mRightarrow{}  ((f[y]  -  f[x])  \mleq{}  (r1/r(n)))))))  and 
                        (((M  *  (b  -  a))  -  k)  \mleq{}  m)) 
              supposing  a  <  b
7.  a  :  \mBbbZ{}
8.  b  :  \mBbbZ{}
9.  a  <  b
10.  k  :  \mBbbN{}\msupplus{}
11.  ((M  *  (b  -  a))  -  k)  \mleq{}  n@0
12.  \mforall{}x,y:\mBbbR{}.
            (((r(a))/k  \mleq{}  x)
            {}\mRightarrow{}  (x  <  y)
            {}\mRightarrow{}  (y  \mleq{}  (r(b))/k)
            {}\mRightarrow{}  ((f[x]  \mleq{}  f[y])  \mwedge{}  (((y  -  x)  \mleq{}  (r1/r(M)))  {}\mRightarrow{}  ((f[y]  -  f[x])  \mleq{}  (r1/r(n))))))
13.  f[(r(a))/k]  \mleq{}  z
14.  z  \mleq{}  f[(r(b))/k]
15.  \mneg{}((M  *  (b  -  a))  \mleq{}  k)
\mvdash{}  \mexists{}c:\mBbbZ{}.  (\mexists{}j:\mBbbN{}\msupplus{}  [((|f[(r(c))/j]  -  z|  \mleq{}  (r1/r(n)))  \mwedge{}  ((r(a))/k  \mleq{}  (r(c))/j)  \mwedge{}  ((r(c))/j  \mleq{}  (r(b))/k))])
By
Latex:
((Evaluate  \mkleeneopen{}m  =  (a  +  b)\mkleeneclose{}\mcdot{}  THENA  Auto)
  THEN  (Evaluate  \mkleeneopen{}j  =  (2  *  k)\mkleeneclose{}\mcdot{}  THENA  Auto)
  THEN  (InstLemma  `nearby-cases`  [\mkleeneopen{}n\mkleeneclose{};\mkleeneopen{}f[(r(m))/j]\mkleeneclose{};\mkleeneopen{}z\mkleeneclose{}]\mcdot{}  THENA  Auto)
  THEN  SplitOrHyps)
Home
Index